Prediction of the Time of Cardiac Function Normalization after Surgery under Extracorporeal Circulation - L. A. Krichevsky; I. A. Kozlov (Общая реаниматология, 2007)
Objective: to study the prognostic value and correlations of hemodynamic parameters during operations under extracorporeal circulation (EC), as well as the possibilities of mathematically predicting the time that takes to recover the normal function of the heart operated on.Subjects and methods: Ninety-three patients (88 males and 5 females) who had undergone myocardial revascularization under EC were examined. The standard intraoperative monitoring involved pulmonary arterial catheterization and transesophageal echocardiography (TEEcho-CG) The duration of postopertative inotropic therapy was recorded. Multiple linear regression analysis was used to comparatively assess the prognostic value of hemodynamic parameters.Results: At the end of surgery, left ventricular ejection fraction, pulmonary artery wedge pressure, and cardiac index were established to be significant predictors of the duration of using cardiotonics. The analysis permitted the prognostic value of the established hemodynamic predictors to be depicted as a linear regression equation. It was shown to be clinically applied.Conclusion. The study revealed the significant intraoperative hemodynamic predictors of recovery of the function of the myocardium after its revascularization under EC. The proposed procedure for interpreting the data obtained, by using a Swan-Ganz catheter and TEEcho-CG, predicts the duration of required sympathomimetic therapy and hence the time of recovery of normal function of the heart operated on.